Popular justice and the regulation of trade: muckraking, rough music, political cartoons and the vilification of entrepreneurial heroes. Issue 2 (3rd July 2018) - Harding, Christopher
ABSTRACT: The discussion here explores the way in which forms of 'popular' justice have been used either preceding or instead of formal processes of accountability and legal control, with particular reference to changes in trading practices in the later nineteenth and earlier twentieth centuries. At that time economic monopolisation and entrepreneurial innovation and wealth accumulation in industrialised countries such as Britain and the United States provoked a considerable degree of popular and community protest, which tested both economic and normative argument. This protest took a number of forms, notably muckraking journalism, political cartoons, and rough music or charivari. Frequently, this protest would target leading entrepreneurial individuals of the time, such as John D Rockefeller, Andrew Carnegie, William Lever and William Whiteley, in turn raising questions about individual and corporate responsibility for the alleged normative violations and abuse of monopoly power. The effect and dynamic of these instances of popular justice are analysed, leading to some reflection as to whether they were characteristic of their time and how they rehearsed argument which now underpins a massive contemporary structure of formal regulation.